(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the technical and economic performance of Uroclhoa brizantha cv. Marandu in the Acre Valley region, from August 2011 to June 2012. The treatments consisted of seven nitrogen doses (0; 33.75; 67.50; 101.25; 135.00; 168.75 and 202.50kg N/ha/year), corresponding to 0; 75; 150; 225; 300; 375 and 450kg urea/ha respectively. The applications were carried out at haul, distributed in three stages. With the increase of nitrogen dosages, nonlinear increase in dry matter, crude protein, ash and ether extract was observed in the analyzed samples, which presented good parameters of nutritional value and development. The nitrogen dosage that obtained the best performance in relation to the cost of nitrogen fertilization was 67.50kg N/ha, as it presented the best production costs (U 49.86 DM and U 30.36 CP) becoming the most economically advantageous option. The nitrogen dosage that presented the best agronomic performance was 168.75Kg N/ha, with crude protein value of 17.78%. The nutritional and developmental parameters of tropical forage U. brizantha cv. Marandu used in the Acre Valley region showed satisfactory agronomic performance.